Local Wisdoms in Bengkulu Play Script “Sayembara Putri Gading Cempaka” by Agus Setiyanto - Dedi Febriyanto; Mulyanto Widodo (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2021)
The purpose of this research is to describe the local wisdom in the Bengkulu play script